Knowledge, attitude, and practices of medical practitioners toward vitamin A prophylaxis in the under-six population: a cross-sectional study on the awareness-knowledge-practice gap - Magar, S. G.; Athalekar, A. Y.; Akunuri, K.; Thakre, S. R. (International Journal of Contemporary Pediatrics, 2026)
Background: The national prophylaxis programme against nutritional blindness due to vitamin A deficiency (VAD) was launched in 1970 as a remedial measure to reduce the blindness due to xerophthalmia and VAD. A decline in the trend of VAD has been documented in India. We investigated the current knowledge, attitude and practices towards vitamin A supplementation in different group of health care practitioners. Methods: A descriptive cross-sectional study was conducted at MGM Medical College and Hospital. Data was collected from medical professionals via a structured Google Forms questionnaire focusing on the dosage, frequency, and practice of clinical implementation of vitamin A prophylaxis. Results: The majority of participants practiced in urban/city areas (89.2%) and were based in Institutional Teaching settings (56.6%). While general awareness of the vitamin A prophylaxis program was nearly universal (92.8%) and most correctly identified the oral route (97.6%), significant knowledge gaps existed regarding specific protocols. Only 10.8% correctly identified the standard 2,00,000 IU dose for the target age group, and only 46.9% agreed on a 6-month schedule. Statistical analysis showed no significant association between the type of institute and awareness (p=0.304) or prescribing habits (p=0.603). However, a statistically significant difference was found in the ability to enumerate laboratory tests for documenting deficiency (p=0.004), with practitioners in teaching institutes showing a higher deficit in specific diagnostic knowledge compared to private practitioners. Conclusions: This study concludes that while pediatricians and medical practitioners have high awareness of vitamin A prophylaxis, there is a clear need for reformation of vitamin A prophylaxis program reinforcement. The presence of clinical Bitot’s spots in daily practice highlights that VAD is still a concern. As there is an ongoing debate about the policy implementation, it is best recommended for medical practitioners to be well aware and educated about the administration of vitamin A prophylaxis. Strengthening food-based strategies and fortification may offer a long-term path forward, but the current clinical reliance on prophylaxis suggests that the transition must be managed carefully to avoid a resurgence of nutritional blindness.